Characteristics and position of maxillary canine impaction using panoramic radiograph at RSGMP UNHAS: a retrospective study - Krimadi, Christine Elisabeth; Yunus, Barunawaty; Masyrifah, Nurul (Ikatan Radiologi Kedokteran Gigi Indonesia, 2025)
Objectives: To analyze cases of maxillary canine impaction, emphasizing characteristics, positional forms, and radiographic features. Materials and Methods: This descriptive study utilized a retrospective and cross-sectional design approach. Samples were obtained through purposive sampling. Secondary data from the Dental Hospital and Education Clinic (RSGMP) at Hasanuddin University from January to December 2023 were used. A total of 43 clinically and radiographically diagnosed cases were included in this study. Results: This study revealed that patients with maxillary canine impaction were predominantly in the age group of 10–19 years (46.5%), with females comprising 62.8% and males comprising 37.2%, resulting in a male-to-female ratio of 1:1.68. Type II maxillary canine impaction (Yamamoto classification) was the most common case, accounting for 53%. Conclusion: Radiography was a crucial aid for diagnosing various types of oral lesions, especially those involving bones. Keywords: Maxillary, maxillary canine impaction, prevalence, radiographic appearance